AHMAD TOSHKOPRIZODA’S “SCIENCE OF WORDS” CLASSIFICATION (TAMADDUN NURI JURNALI, 2024)
By the present time, the classification of sciences has become perfect. Such perfection is influenced by historical traditions, research and innovations in the classification of sciences. Among these, Akhmad Tashkuprizada’s work “Mawduat al-ulum” also has an important place. This article analyzes the “Science of Words” classified in Akhmad Tashkuprizada’s work “Mawduat al-ulum”.